RESERVOIR CHARACTERISTICS AND 2D-CONNECTIVITY MODELING OF NEOGENE SILICICLASTIC SHALLOW-MARINE SUCCESSIONS OF SARA W AK AND SABAH. MALAYSIA - SIDDIQUI, NUMAIR AHMED (2016)
Sedimentological characteristics and pnmary depositional architecture of siliciclastic shallow-marine reservoirs in terms of reservoir heterogeneities and connectivity can improve the understanding of subsurface reservoir quality. Traditional datasets used in reservoir modeling (i.e. seismic and well data) cater a detenninistic architectural framework with detailed facies and petrophysical description only at discrete locations. There exists uncertainty associated with heterogeneities pertinent to the sandstone facies distribution. The ability of outcrop exposure to study the sedimentary architecture (e.g. stacking patterns, lateral continuation, facies proportions and distribution) at a wide range of scales and type of reservoir heterogeneities (field/ outcrop scale to micro scale) for reservoir connectivity and 20 modeling make them ideal analogues for reservoir studies.